ANALISA PERUBAHAN DEBIT TERHADAP KEHILANGAN TEKANAN PADA PERUBAHAN PENAMPANG ALAT UJI SISTEM ALIRAN FLUIDA MENGGUNAKAN PIPA GALVANIS SKALA LABORATORIUM - zulhadi ,; Eko Julianto; M Zulyan (Suara Teknik : Jurnal Ilmiah, 2020)
Fluid mechanics is a subdiscipline of continuum mechanics that studies fluid (can be liquid and gas). Fluid itself is a substance that can undergo changes in shape continuously / continuously when exposed to pressure / shear force even though it is relatively small or can also be said to be a substance that flows, whereas such as rocks and hard objects or all solid substances are not classified into the fluid because it cannot flow, this study aims to determine the pressure loss that occurs in the cross section of galvanized pipe with a discharge that is varied using a valve opening 90 °, 60 °, 30. From the research conducted in the test results can be obtained at valve opening 90 with discharge 0 , 00072 m³ / s loses its pressure He 0.4523 (m), valve opening 60 discharge 0,00072 m³ / s loses its pressure He 0,3673 (m), valve opening 30 discharge 0,00051 m³ / s loses its pressure HE 0.1954 (m).